Validity of Study Skill Tests with First Year University Students - Uhlemann, Marx R.; Thompson, Anthony P.; Reberg, Bonnie J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to collect concurrent and predictive validity data for three study skill instruments frequently used for diagnostic purposes in Canadian highschools and universities. The study skill tests examined were the: McGraw-Hill StudySkills Test; McGraw-Hill Inventory of Study Habits and Attitudes; and Study Attitudes and Methods Survey. The concurrent validity results indicated that scales from the McGraw-Hill Study Skills Test and the Study Attitudes and Methods Survey have almost no overlapping dimensions of assessment. Predictive validity results indicated that Grade 13 marks and IQ scores are better indicators of first year university marks than any of the study skill tests examined. The implications of these findings are discussed.